Productivity of Rural Banks in Central Java: Is Technological Changes Matter? - Aisyah As-Salafiyah (Islamic Economics Methodology, 2023)
This study aimed to analyze the level of productivity, the factors that influence it, the potential for improvement needed, and a comparison of the productivity of Rural Banks (BPR) and Islamic Rural Banks (BPRS) in Central Java. This research also looks at the productivity of BPR and BPRS during the Covid-19 pandemic. The research period used in this study is from 2016-2021, with a research sample of 9 BPR and 7 BPRS in Central Java. The analytical method used is a non-parametric approach, namely the Malmquist Productivity Index (MPI), with secondary data sources derived from BPR and BPRS financial reports on the Financial Services Authority (OJK) website. The results of the study show that during the COVID-19 pandemic, BPR and BPRS experienced an increase in productivity in general, where BPRS showed better performance with higher technology adoption and higher average Total Factor Productivity Changes (TFPCH) values, while the change in efficiency (EFFCH) tends to decrease; As a result, BPRS occupy a better position in quadrants 1 and 2 in the division of the four types of BPR and BPRS based on the level of technology and efficiency. This research also provides recommendations to BPR and BPRS practitioners, management, and regulators.